Ideas and Images from Argentina - Glusberg, Jorge; Vere, Philip (New York : Bronx Museum of the Arts, 1989)
Allievi, Fernando ; Alvarez Piñeiro, Emma ; Alvaro, Jorge ; Aro, Elizabeth ; Bedel, Jacques ; Benedit, Luis ; Bertani, Ernesto ; Bessouet, Norma ; Bianchedi, Remo ; Bobbio, Pablo ; Bonevardi, Marcelo ; Cambre, Juan José ; etc.
Ideas and Images from Argentina, The Bronx Museum of the Arts, New York, december 1989 - January 28, 1990
boek
Keywords: Argentinië